Return to Work Assessment in A Financial Analyst with Major Depressive Disorder: A Case Report - Fitria Nanda Saputri; Nuri Purwito Adi (ILUNI MKK FKUI and PRODI MKK FKUI, 2023)
Background: More than half of the global population are workers, and depression and anxiety result in the loss of 12 billion working days per year, costing the global economy around 1 trillion.1 Depression is a widespread mood disorder that can lead to self-harm and suicide.2,3 Work eligibility assessments are essential to ensure that workers can perform their duties safely and effectively. This case report discusses the fitness-to-work assessment of a financial analyst with major depressive disorder with psychotic features. Objective: To explore factors affecting the fit-to-work status of a patient with major depressive disorder and assess the fit-to-work status of the patient.Case Presentation: A 27-year-old female with a history of depression and trauma worked as a financial analyst. She had a psychiatric evaluation revealing major depressive disorder with psychotic features, moderate stressors, narcissistic personality disorder, and problematic workplace relationships.Discussion: PERDOKI has a seven-step process for evaluating fitness to work and return-to-work programs. These steps involve assessing the patient’s medical condition, disability, job demands, risks, and tolerance to determine the appropriate work status. In this case, the patient is declared fit to work with a note.Conclusion: The role of occupational medicine in workers with major depressive disorder is very important, in-depth interviews regarding workload and other factors that are stressors for workers must be carried out. Support from the inner circle, family and workplace is very important for workers with major depressive disorder. Clinical symptoms of delusions, hallucinations and suicidal tendencies are the main criteria for determining return to work in addition to other influential factors.